Effects of S-adenosyl-L-homocysteine and trichostatin A on developmental competence, epigenetic modification, and gene expression in cloned cattle embryos - Jafari, Shahram (2012)
With regards to low efficiency of the somatic cell nuclear transfer (SCNT)procedure the hypothesis that epigenetic marks of somatic donor cells are responsible for this inefficiency is proposed. Epigenetic marks such as DNA methylation and histone acetylation are two major participants in nuclear reprogramming which can be used as indicators to assess SCNT efficiency. For this reason treating somatic cells or embryos with epigenetic drugs immediately after fusion or activation may improve the developmental rate of reconstructed embryos. Therefore, in this study we investigated the effect of S-adenosyl-Lhomocysteine (SAH), a reversible inhibitor of DNA methyltransferases (DNMTs),at different intervals post SCNT on developmental competence, epigenetic status and gene expression of bovine cloned embryos. Treatment with 1mM SAH for 12 hours resulted in 54.6% blastocyst production which was significantly higher (P<0.05) than in vitro fertilized (IVF) embryos (37.2%), cloned embryos treated with SAH for 72 hours (31.0%) and control cloned embryos (34.6%). Intensity of DNA methylation in cloned embryos treated with SAH for 48 h resembled IVF and was significantly lower (P<0.05) than other SCNT groups. The histone H3 Lysine 9 (H3K9) acetylation levels of all SCNT groups were significantly lower (P<O.O5) than the IVF group. The fluorescent intensity of EGFP-POU5F1 reporter gene at all intervals of SAH treatments, except for the 72 hours, was significantly higher (P<0.05) than non-treated SCNT embryos. Real-time analysis of gene expression in cloned blastocysts revealed significantly higher (P<0.05) expression of POU5F1 compared with IVF. There was no effect (P>0.05) of either embryo production method (SCNT vs. IVF), or among SAH treatment interval on the expression of BCL2 gene. On the contrary, treatment with SAH resulted in significant increase (P<0.05) in VEGF expression in comparison with IVF and control SCNT, except for cloned embryos treated with SAH for 24 hours. It was suggested that time interval of DNA methyltransferases (DNMTs) inhibition may have important consequences on the different features of bovine cloned embryos and the improving effects of DNMTs inhibition on developmental competency of cloned embryos is restricted to a specific period of time preceding de novo methylation stage. The effect of 0.05 µM Trichostatin A (TSA), a histone deacetylase inhibitor, post-fusion for 12 h on the diverse aspects of developmental competency in SCNT embryos was investigated. The results of this study showed TSA treatment of SCNT embryos for 12 h after activation, significantly (P<0.05) improve blastocysts rate. A significant reduction and increase (P<0.05) were observed in analyse of DNA methylation and histone acetylation levels respectively in the blastocyst stage of the TSA-treated group which is similar to IVF-derived blastocysts. Finally,examination of blastocysts on day 7 revealed the highest expression of OCT4 in the TSA-treated group (P> 0.05), while there were no significant changes observed in expressions of BCL2 and VEGF. The results of this study indicated that post-fusion treatment with SAH has a time dependent effect on DNA-methylation and histone-acetylation, developmental competence and gene expression of the cloned embryos. The results of this study also showed that treatment of SCNT embryos with TSA after activation increased the capability of the embryos to develop to the blastocyst stage and TSA-treated cloned blastocysts are hypomethylated and hyperacetylated and higher relative expression of POU5F1 and VEGF genes. In addition, these results might improve quality of cloned bovine embryos to produce transgenic cattles.